On Farm Assessment of High Fibre Dietary Sources for Grower and Finisher Ostriches - Glatz, P.C.; Ru, Y.J.; Hastings, M.Y.; Black, D.; Rayner, B. (International Journal of Poultry Science, 2003)
Feed comprises over 60% of the cost of growing ostriches to slaughter weight. Any saving in feed costs would contribute greatly to the overall profitability of the ostrich industry. Very cheap sources of fibre are available to feed ostriches in Australia. The purpose of these experiments was to examine; i) the role of fibre digesting enzymes in improving the utilization of lucerne silage and ii) to provide information on the role of lucerne silage, lucerne and pea straw in supplementary diets. The first trial compared the growth of ostriches from 32-36 weeks-of-age fed a commercial finisher diet (with and without a glycanase enzyme) with a lucerne silage diet (also with or without enzyme supplementation). The birds on the silage diet (with enzyme) had a significantly (P